let X be non empty set ; :: thesis: for S being SigmaField of X
for M being sigma_Measure of S
for E being Element of S
for f being nonpositive PartFunc of X,ExtREAL st ex A being Element of S st
( A = dom f & f is A -measurable ) holds
( Integral (M,f) = - (integral+ (M,(max- f))) & Integral (M,f) = - (integral+ (M,(- f))) & Integral (M,f) = - (Integral (M,(- f))) )

let S be SigmaField of X; :: thesis: for M being sigma_Measure of S
for E being Element of S
for f being nonpositive PartFunc of X,ExtREAL st ex A being Element of S st
( A = dom f & f is A -measurable ) holds
( Integral (M,f) = - (integral+ (M,(max- f))) & Integral (M,f) = - (integral+ (M,(- f))) & Integral (M,f) = - (Integral (M,(- f))) )

let M be sigma_Measure of S; :: thesis: for E being Element of S
for f being nonpositive PartFunc of X,ExtREAL st ex A being Element of S st
( A = dom f & f is A -measurable ) holds
( Integral (M,f) = - (integral+ (M,(max- f))) & Integral (M,f) = - (integral+ (M,(- f))) & Integral (M,f) = - (Integral (M,(- f))) )

let E be Element of S; :: thesis: for f being nonpositive PartFunc of X,ExtREAL st ex A being Element of S st
( A = dom f & f is A -measurable ) holds
( Integral (M,f) = - (integral+ (M,(max- f))) & Integral (M,f) = - (integral+ (M,(- f))) & Integral (M,f) = - (Integral (M,(- f))) )

let f be nonpositive PartFunc of X,ExtREAL; :: thesis: ( ex A being Element of S st
( A = dom f & f is A -measurable ) implies ( Integral (M,f) = - (integral+ (M,(max- f))) & Integral (M,f) = - (integral+ (M,(- f))) & Integral (M,f) = - (Integral (M,(- f))) ) )

assume ex A being Element of S st
( A = dom f & f is A -measurable ) ; :: thesis: ( Integral (M,f) = - (integral+ (M,(max- f))) & Integral (M,f) = - (integral+ (M,(- f))) & Integral (M,f) = - (Integral (M,(- f))) )
then consider A being Element of S such that
A2: ( A = dom f & f is A -measurable ) ;
A3: dom (max+ f) = A by ;
A4: f = - (max- f) by Th32;
then A5: - f = max- f by Th36;
for x being Element of X st x in dom (max+ f) holds
(max+ f) . x = 0
proof
let x be Element of X; :: thesis: ( x in dom (max+ f) implies (max+ f) . x = 0 )
assume x in dom (max+ f) ; :: thesis: (max+ f) . x = 0
then f . x = - ((max- f) . x) by ;
then - (f . x) = (max- f) . x ;
hence (max+ f) . x = 0 by MESFUNC2:21; :: thesis: verum
end;
then A6: integral+ (M,(max+ f)) = 0 by ;
A7: Integral (M,f) = (integral+ (M,(max+ f))) - (integral+ (M,(max- f))) by MESFUNC5:def 16
.= (integral+ (M,(max+ f))) + (- (integral+ (M,(max- f)))) by XXREAL_3:def 4 ;
hence Integral (M,f) = - (integral+ (M,(max- f))) by ; :: thesis: ( Integral (M,f) = - (integral+ (M,(- f))) & Integral (M,f) = - (Integral (M,(- f))) )
thus A8: Integral (M,f) = - (integral+ (M,(- f))) by ; :: thesis: Integral (M,f) = - (Integral (M,(- f)))
A = dom (- f) by ;
hence Integral (M,f) = - (Integral (M,(- f))) by ; :: thesis: verum